1995
DOI: 10.1130/0016-7606(1995)107<1211:faaciy>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Fire and alluvial chronology in Yellowstone National Park: Climatic and intrinsic controls on Holocene geomorphic processes

Abstract: We employed a systemwide approach, a large and robust set of radiocarbon ages, and modern process analogs to interpret the Holocene history of forest fire-related sedimentation and overall alluvial activity in northeastern Yellowstone National Park. Debris-flow and flood events following the 1988 fires provided facies models for interpreting the stratigraphic record of fire-related sedimentation within valley-side alluvial fans of Soda Butte Creek. Fire-related deposits make up approximately 30% of the late Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
237
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 214 publications
(248 citation statements)
references
References 52 publications
6
237
0
Order By: Relevance
“…Millspaugh et al (1998) suggested a trend related primarily to solar insolation, though more detailed dating suggests a link to millennial-scale phenomena (see also Meyer et al 1995). The results of Meyer et al (1995), discussed by Meyer and Pierce (2003), suggest an anti-correlation with Bond cycles and also a response to century-scale events such as the MWP and the Little Ice Age.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Millspaugh et al (1998) suggested a trend related primarily to solar insolation, though more detailed dating suggests a link to millennial-scale phenomena (see also Meyer et al 1995). The results of Meyer et al (1995), discussed by Meyer and Pierce (2003), suggest an anti-correlation with Bond cycles and also a response to century-scale events such as the MWP and the Little Ice Age.…”
Section: Discussionmentioning
confidence: 99%
“…in Yellowstone (Meyer et al 1995;Millspaugh et al 2000), Idaho (Meyer et al 2001), Oregon (Long et al 1998), southwestern BC (Gavin et al 2003b;Hallett et al 2003a;Lertzman et al 2002), and southeastern BC (Hallett and Walker 2000;Hallett et al 2003b). This signal appears less marked in the tropics (Horn and Sanford 1992;Turcq et al 1998) and in other mid-latitude regimes, such as in eastern Canada (Carcaillet et al 2001) and New Zealand (Molloy et al 1963).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations